2009
DOI: 10.1159/000232165
|View full text |Cite
|
Sign up to set email alerts
|

TSH Levels in Relation to Gestation, Birth Weight and Sex

Abstract: Aims: Low birth weight is associated with hypothyroidism and an adverse metabolic profile in later life. Our aim was to examine the relationship between neonatal TSH and birth weight, gestational age and sex. Methods: We compared blood spot filter paper TSH levels with birth weight, gestational age and sex in a 10% sample of infants screened for congenital hypothyroidism at a single centre in Northern England. All gestational ages were included with infants suspected of having congenital hypothyroidism exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
(24 reference statements)
2
9
2
1
Order By: Relevance
“…However, these studies measured TSH levels around the 6 th day of life, whereas our study measured infants between day of life 1 and 3, but primarily on day 1 of life. Studies examining cord blood levels or levels obtained soon after delivery have observed similar results to ours (5, 6, 25). …”
Section: Discussionsupporting
confidence: 87%
“…However, these studies measured TSH levels around the 6 th day of life, whereas our study measured infants between day of life 1 and 3, but primarily on day 1 of life. Studies examining cord blood levels or levels obtained soon after delivery have observed similar results to ours (5, 6, 25). …”
Section: Discussionsupporting
confidence: 87%
“…This result was different from the one found by Korada et al in United Kingdom where male gender have had a higher median TSH value [23]. This difference can be explained by the high proportion of male gender in their study compared to ours.…”
Section: Discussioncontrasting
confidence: 99%
“…This weak correlation and low-shared variance can be explained by the small size of our sample. This result is opposed to Korada et al findings where higher TSH were found in the lowest birth weight categories [23] This difference can be explained by the fact that all gestational age where included in the study also inclusive of preterm. It is well known that premature babies are high risk of morbidity and mortality, and illness is another shape of stress [25].…”
Section: Discussioncontrasting
confidence: 95%
“…Contudo, sugere-se padronizar a época de coleta das amostras, em vez de utilizar valores de corte variados (30,33). Além da coleta muito precoce da amostra de TSH-F, outros podem ser os fatores responsáveis por resultados falso-positivos desse exame, como o caso de prematuridade, gemelaridade ou presença de retardo de crescimento intrauterino (34,35). Em nosso trabalho, não temos o levantamento de todos esses dados.…”
Section: Discussionunclassified